1988
DOI: 10.1159/000120369
|View full text |Cite
|
Sign up to set email alerts
|

Diastematomyelia – A 40-Year Experience

Abstract: Diastematomyelia is a rare but potentially devastating spinal dysraphism classically characterized as a bony or fibrous spur separating two hemispinal cords. This study reviews our experience with diastematomyelia over a 40-year period from 1947 through 1987, and suggests that the neurologic and orthopedic deficits of diastematomyelia remain stable during extended follow-up after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 22 publications
(27 reference statements)
3
29
0
1
Order By: Relevance
“…Sensory improvement was noted in 4/12 of patients with preoperative sensory disturbances. The chances of autonomic improvement are still lower, reportedly in the range of 15–40% [10,11,12,13,14]. In the present series, autonomic disturbances improved in 2/12 patients.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Sensory improvement was noted in 4/12 of patients with preoperative sensory disturbances. The chances of autonomic improvement are still lower, reportedly in the range of 15–40% [10,11,12,13,14]. In the present series, autonomic disturbances improved in 2/12 patients.…”
Section: Discussionmentioning
confidence: 42%
“…Deficits also depend on the associated anomalies like syringomyelia, lipomeningomyelocele and congenital tumors such as dermoids and epidermoids. Overall, the outcome also depends on anomalies of other systems [2, 4, 10, 11]. …”
Section: Discussionmentioning
confidence: 99%
“…The frequency of composite-type SCM was less than 1% in the series reported by Harwood-Nash and McHugh [16]. Gower et al [17] had only 1 patient with composite-type SCM with a bone spur at the midcleft and another at the caudal end of the cleft. Erşahin et al [18] also reported on 3 unusual cases of SCM, 2 of which were composite type.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations include cutaneous abnormality overlying the spine, neurologic deficits and orthopedic abnormalities. [1][2][3][4] Clinically, the symptomatology is not specific and does not differ from that seen in other forms of spinal dysraphism. [5][6][7][8] Despite its low incidence, diastematomyelia results in severe neurological dysfunction.…”
Section: Introductionmentioning
confidence: 99%